HFE gene mutations in Brazilian thalassemic patients - Oliveira, T. M.; Souza, F. P.; Jardim, A. C. G.; Cordeiro, J. A.; Pinho, J. R. R.; Sitnik, R.; Estevão, J. F.; Bonini-Domingos, C. R.; Rahal, Paula [UNESP] (My University, 2006)
Hereditary hemochromatosis is a disorder of iron metabolism characterized by increased iron intake and progressive storage and is related to mutations in the HFE gene. Interactions between thalassemia and hemochromatosis may further increase iron overload. The ethnic background of the Brazilian population is heterogeneous and studies analyzing the simultaneous presence of HFE and thalassemia-related mutations have not been carried out. The aim of this study was to evaluate the prevalence of the H63D, S65C and C282Y mutations in the HFE gene among 102 individuals with alpha-thalassemia and 168 beta-thalassemia heterozygotes and to compare them with 173 control individuals without hemoglobinopathies. The allelic frequencies found in these three groups were 0.98, 2.38, and 0.29% for the C282Y mutation, 13.72, 13.70, and 9.54% for the H63D mutation, and 0, 0.60, and 0.87% for the S65C mutation, respectively. The chi-square test for multiple independent individuals indicated a significant difference among groups for the C282Y mutation, which was shown to be significant between the beta-thalassemia heterozygote and the control group by the Fisher exact test (P value = 0.009). The higher frequency of inheritance of the C282Y mutation in the HFE gene among beta-thalassemic patients may contribute to worsen the clinical picture of these individuals. In view of the characteristics of the Brazilian population, the present results emphasize the need to screen for HFE mutations in beta-thalassemia carriers.
Keywords: C282Y; H63D; HFE; S65C; Thalassemia; HFE protein; alpha thalassemia; beta thalassemia; Brazil; chi square test; clinical feature; controlled study; female; Fisher exact test; gene frequency; gene mutation; hemoglobinopathy; heterozygote; human; inheritance; major clinical study; male; prevalence; thalassemia; alpha-Thalassemia; beta-Thalassemia; Case-Control Studies; Female; Gene Frequency; Genotype; Heterozygote; Histocompatibility Antigens Class I; Humans; Male; Membrane Proteins; Mutation; Polymerase Chain Reaction